Cytological analysis of breast lesions: a review of 780 cases - Jayaram, G.; Alhady, S.F.; Yip, C.H. (College of Pathologists, Academy of Medicine Malaysia, 1996)
780 breast cytology samples obtained over a one year period at the Breast Clinic of the University Hospital, Kuala Lumpur were reviewed. These included 745 fine needle aspirates (FNA's) and 35 nipple smears. The broad categories of cytodiagnoses were as follows: malignant: 95, suspicious or equivocal: 26, benign: 543, no proliferative lesion: 58 and inadequate: 58. The benign and malignant lesions were also subcategorized on cytological basis. The suspicious or equivocal lesions were subjected to biopsy and 17 of these proved to be malignant. 194 cases that were subjected to histological confirmation and 34 cases that were considered to be undisputably malignant (on the basis of clinical features, recurrences, metastases, etc.) were subjected to statistical analysis (total 228 cases). If the cytologically suspicious/equivocal category was considered as "test positive" the sensitivity of cytodiagnosis was 97.4% and the specificity 92%. The high degree of cytodiagnostic sensitivity and specificity make breast cytology a valuable adjunct in the evaluation of breast lesions.